2021
DOI: 10.3329/bpj.v24i1.51630
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cytotoxicity of Selected Mikania species using Brine Shrimp Lethality Bioassay and Sulforhodamine B (SRB) Assay

Abstract: This study aims to assess the comparative cytotoxic activity of the ethanolic extract of Mikania cordata (MC), Mikania micrantha (MM) and Mikania scandens (MS) (Family: Asteraceae) using brine shrimp lethality bioassay and colorimetric sulforhodamine B assay method. In SRB assay, A549 human lung carcinoma, SK-Mel-2 skin melanoma and B16F1 mouse melanoma cell lines were used. In brine shrimp assay, the LC50 for MC, MM, MS and vincristine were found to be 29.04, 15.84, 32.35, and 1.2 μg/ml, respectively. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In vivo lethality in basic zoological species can be utilized as a useful monitor for screening and fractionation in the search for new bioactive natural compounds [32]. Lethality of substances to brine shrimp nauplii has been linked to the probable ability of such compounds to kill cancer cells in cell cultures [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo lethality in basic zoological species can be utilized as a useful monitor for screening and fractionation in the search for new bioactive natural compounds [32]. Lethality of substances to brine shrimp nauplii has been linked to the probable ability of such compounds to kill cancer cells in cell cultures [32].…”
Section: Discussionmentioning
confidence: 99%
“…The volume was made up to 5 mL with seawater (38 g/L, pH 7.4) and the vials were incubated at 25-27⁰C for 24 h under illumination. Other vials containing seawater and the reference cytotoxic drug (etoposide) served as the negative and positive controls respectively [32].…”
Section: Determination Of Cytotoxic Effects Of O Basilicum Oil On Bri...mentioning
confidence: 99%
“…The SRB (colorimetric sulforhodamine B assay) method designed by Khatun et al, 18 and described by Skehan et al, 19 was used to assess cytotoxicity against mouse Hela cell lines provided by the cell bank of the ICCBS. The rapidly growing exponential cells were harvested and suspended in growth media in a 96-well plate (100 mL, RPMI1640).…”
Section: Sulforhodamine-b Antiproliferative Assaymentioning
confidence: 99%
“…Levan possesses anti-inflammatory properties. After treating splenocytes from BALB/c mice with varying quantities of an exopolysaccharide (EPS) produced from Bacillus licheniformis, cell survival evaluated by using the 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) test, The findings revealed an increase in the reproduction of splenocytes (splenic phagocytic cells [49] Srikanth [7] investigated levan's anti-inflammatory properties. They compared levan to diclofenac sodium, a well known anti-inflammatory medication.…”
Section: Levan As An Anti-inflammatorymentioning
confidence: 99%
“…Furthermore, a research published by Xu [3] using levan from Paenibacillus bovis found a significant increase in spleen lymphocyte proliferation as well as a change in cytokine production during levan treatment [49]. Study determined that following the addition, the levels of necrosis tumor factor alpha (TNFa) increased.…”
Section: Levan As An Anti-inflammatorymentioning
confidence: 99%